Hybrid learning models based on ICT: theoretical and applied aspects in Uzbekistan’s higher education (MMIT Proceedings, 2025)
This article explores the development of hybrid learning models grounded in information and communication technologies (ICT), with a focus on their theoretical underpinnings and practical implementation in Uzbekistan’s higher education sector. It reviews key theoretical frameworks for hybrid (blended) learning and ICT integration, examines current trends and practices in Uzbek universities, and analyzes available empirical data and case studies on digital education initiatives. The discussion highlights both challenges – such as infrastructure gaps, faculty readiness, and quality assurance issues – and opportunities – including expanded access and enhanced learning outcomes – associated with hybrid education in the region. The article also details recent policy initiatives, institutional strategies, and pilot projects launched in Uzbekistan to support ICT-enhanced hybrid learning. Finally, it offers conclusions and recommendations for leveraging ICT to further improve and sustain hybrid higher education in Uzbekistan